Minimally Invasive 360° Fusion Using a Combination of INFIX and Minimally Invasive Spinopelvic Fixation by Intraoperative Computed Tomography Navigation for Unstable Pelvic Ring Fracture: A Technical Note - Akihiko Hiyama; Taku Ukai; Shota Ogasawara; Tatsumi Tanaka; Masahiko Watanabe (Orthopaedic Surgery, 2023)
Objective Fluoroscopy is often used in the surgery of unstable pelvic ring fractures, and improved safety in implant placement is an issue. An anterior subcutaneous pelvic fixator (INFIX) combined with a percutaneous screw has been reported to be a minimally invasive and effective surgical technique for unstable pelvic ring injuries. However, although percutaneous screw fixation is minimally invasive, its indications for fracture fixation and fractures with large fragment displacements in the vertical plane remain controversial. Therefore, this technical note aims to describe a new technique for unstable pelvic ring fractures. Methods We describe a 360° fusion of the pelvic ring to treat unstable pelvic ring fractures, including vertical shear pelvic ring fractures, using an intraoperative CT navigation system. Seven patients were treated with 360° fusion for type C pelvic ring fractures. In surgery, after reducing the fracture with external fixation, intraoperative CT navigation is used to perform a 360° fusion with INFIX and minimally invasive surgical spinopelvic fixation (MIS‐SPF). We will introduce a typical case and explain the procedure. Results A 360° fixation was performed, and no perioperative complications were noted. The mean blood loss was 253.2 ± 141.0 mL, and the mean operative time was 224.3 ± 67.4 min. In a typical case, bone union was obtained 1 year after surgery, and we removed all implants. Conclusions MIS‐SPF has a strong fixation force and helps reduce fractures' horizontal and vertical planes. In addition, 360° fusion with intraoperative CT navigation may help treat unstable pelvic ring fractures.